Associations of soluble fms-like tyrosine kinase-1 with cardiovascular events and stroke in patients with atrial fibrillation and suspected or known coronary artery disease: the EXCEED-J study. (3rd October 2022) - Wada, H; Shinozaki, T; Suzuki, M; Sakagami, S; Ajiro, Y; Funada, J; Matsuda, M; Shimizu, M; Takenaka, T; Morita, Y; Wada, K; Kotani, K; et al.
Abstract: Background: Atrial fibrillation (AF) increases the risk of stroke. Soluble fms-like tyrosine kinase-1 (sFlt-1), a vascular endothelial growth factor (VEGF) antagonist, has been suggested as a marker of endothelial dysfunction, which are associated with both AF and coronary artery disease (CAD). Recently, we demonstrated that sFlt-1 is independently associated with major adverse cardiovascular (CV) events (MACE) in patients with suspected or known CAD. However, the prognostic utility of sFlt-1 in patients with AF remains unknown. Methods: Using data from a multicenter, prospective cohort of 3255 patients with suspected or known CAD, we investigated whether AF modifies the prognostic utility of sFlt-1. Heparin-free serum levels of sFlt-1, N-terminal pro-brain natriuretic peptide, high-sensitivity cardiac troponin-I, high-sensitivity C-reactive protein, cystatin C, neutrophil gelatinase-associated lipocalin, VEGF, and placental growth factor were measured in 324 patients with AF and 2931 patients without AF. The primary outcome was MACE defined as a composite of CV death, nonfatal myocardial infarction, and nonfatal stroke. The secondary outcomes were all-cause death, CV death, stroke, heart failure (HF) hospitalization, and coronary/peripheral artery revascularization. The biomarkers were natural log-transformed for use as continuous variables. Results: After adjustment for potential clinical confounders including anticoagulant drug use, sFlt-1 was significantly associated with MACE (hazard ratio for 1 standard deviation increase [HR], 1.55; 95% confidence interval [CI], 1.14–2.08), CV death (HR, 1.68; 95% CI, 1.10–2.48), and stroke (HR, 1.89; 95% CI, 1.16–3.10), but not with all-cause death (HR, 1.32; 95% CI, 0.99–1.73), HF hospitalization (HR, 0.97; 95% CI, 0.73–1.25), or revascularization (HR, 0.99; 95% CI, 0.74–1.28) in patients with AF, whereas sFlt-1 was significantly associated with MACE (HR, 1.19; 95% CI, 1.02–1.37), all-cause death (HR, 1.19; 95% CI, 1.05–1.34), CV death (HR, 1.26; 95% CI, 1.03–1.48), and HF hospitalization (HR, 1.26; 95% CI, 1.11–1.42), but not with stroke (HR, 1.06; 95% CI, 0.81–1.33) or revascularization (HR, 1.01; 95% CI, 0.95–1.07) in patients without AF. Among other biomarkers, only VEGF was significantly associated with MACE (HR, 1.55; 95% CI, 1.02–2.44), and no biomarkers were significantly associated with CV death or stroke in patients with AF. sFlt-1 added incremental prognostic information for MACE (P=0.005 for net reclassification improvement [NRI], P=0.026 for integrated discrimination improvement [IDI]) and stroke (P=0.034 for NRI, P=0.018 for IDI), but not for CV death (P=0.021 for NRI, P=0.134 for IDI), to the model with potential clinical confounders in patients with AF. Conclusions: sFlt-1 independently predicted MACE and stroke in patients with AF and suspected or known CAD. sFlt-1 may serve as a novel prognostic biomarker to stratify the risk of MACE and stroke in patients with AF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Health Labour Sciences Research Grant (2013-2014), AMED (2015-2017, Grant Number JP17ek0210008)